Lexicografia i variació funcional - Payrató, Lluís (Caplletra. Revista Internacional de Filologia, 2015)
This paper reviews the basic concepts related to notions of variation and functional variation, in particular register, and it questions whether these concepts have been taken into account by the lexicographic tradition. The paper focuses on which are the most suitable marks to recognize several aspects connected with the usage of lexical items: on the one hand the field (topic), the mode (channel), the tenor (purpose), and the tone (formality), as the register’ s components; and on the other hand, various factors concerning cultural, enunciative, and textual grounds.